2015
DOI: 10.1097/ana.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

ProSeal Laryngeal Mask Airway Attenuates Systemic and Cerebral Hemodynamic Response During Awakening of Neurosurgical Patients

Abstract: Replacing the ETT with the LMA before neurosurgical patients emerge from anesthesia results in a more favorable hemodynamic profile, less cerebral hyperemia, and a lower incidence of cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
2
11
2
Order By: Relevance
“…These ndings contrast with the different hemodynamic pro le of our previous study performed in patients after supratentorial craniotomy with a similar protocol. [8] In our former clinical trial on supratentorial craniotomy patients, baseline mean arterial pressure was lower than in this present study (about 20 mmHg lower). We speculate that the preoperative administration of a quite high dose of xylometazoline could provoke a similar mild hypertensive effect in all included patients.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These ndings contrast with the different hemodynamic pro le of our previous study performed in patients after supratentorial craniotomy with a similar protocol. [8] In our former clinical trial on supratentorial craniotomy patients, baseline mean arterial pressure was lower than in this present study (about 20 mmHg lower). We speculate that the preoperative administration of a quite high dose of xylometazoline could provoke a similar mild hypertensive effect in all included patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Our group showed that neurosurgical patients emerged from anesthesia with a more favorable hemodynamic pro le, a lower incidence of coughing and less cerebral hyperemia when a LMA was placed just after removal of the endotracheal tube (ETT) but before emergence after undergoing a supratentorial craneotomy. [8] The transnasal transsphenoidal endoscopic approach has been reported to have less associated morbidity than open surgery, [9][10] but postoperative cerebrospinal uid (CSF) leakage remains a major limitation of this technique. [11] The incidence of CSF leakage was 8% in a patient series in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Perell o-Cerda`et al 1 reported that before the end of neurosurgery, replacing the endotracheal tube with a LMA can avoid severe fluctuations of hemodynamic parameters during extubation. In our study, the MAP and HR in the ETI group were 5 to 6 mmHg and 11 to 15 bpm higher compared with the LMA group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies utilising the replacement of ETT has been conducted in anaesthetised and paralysed neurosurgical patients as it has been associated with favourable haemodynamic profile, less cerebral hyperaemia and a lower incidence of cough but may fret with the inadvertent risk of losing airway. [ 15 16 ] Similarly, the studies utilising such replacement in thyroidectomy were performed again in anaesthetised and paralysed patients[ 8 14 ] except a case report by Maroof et al . [ 7 ] where it was performed following reversal of neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%